If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-9)=4x
We simplify the equation to the form, which is simple to understand
5(x-9)=4x
Reorder the terms in parentheses
+(+5x-45)=4x
Remove unnecessary parentheses
+5x-45=+4x
We move all terms containing x to the left and all other terms to the right.
+5x-4x=+45
We simplify left and right side of the equation.
+1x=+45
We divide both sides of the equation by 1 to get x.
x=45
| 5x-45=4x | | 4x^4-8x^3+5x^2-x-1=0 | | (4x^3-8x^2+5x-1)=0 | | 8y-9x-1=0 | | 15p+40= | | 5-p=-2 | | -19v-18=-16v+3 | | -19v-18=16v+3 | | 4v^3+6v^2-4v=0 | | 2y^2=32 | | 3x-7=9x+18 | | 2x+10=3x-22 | | 5(3n-1)=80 | | S=35+14t-2t | | rX^2-37x-36=0 | | 7x+1=3x+19 | | 7x-1=3x+19 | | 2x+(x-6)=3x-(4x-6) | | 18=3(25t+2) | | P(4)=x^3-4x^2+8 | | 6=10-2a | | 6x+1=x+7 | | 4=x-0.6 | | x^2(x^2+1)-3(2x^2+1)+9=0 | | 6t^2-38t-28=0 | | X(x+15)=95 | | 12x-9=7x+4x-2 | | 12x-9=7x | | -2(x+3)-4(x-5)=-2x+1 | | -2(-x+3)-4(x-5)=2x+1 | | 2x(5x-4)-6(6-3x)= | | 4x(6x-5)-5(3-5x)= |